Recent advances in poor HIV immune reconstitution: what will the future look like? - Zhang, Wenyuan; Ruan, Lianguo (Frontiers in Microbiology, 2023)
Combination antiretroviral therapy has demonstrated proved effectiveness in suppressing viral replication and significantly recovering CD4+ T cell count in HIV type-1 (HIV-1)-infected patients, contributing to a dramatic reduction in AIDS morbidity and mortality. However, the factors affecting immune reconstitution are extremely complex. Demographic factors, co-infection, baseline CD4 cell level, abnormal immune activation, and cytokine dysregulation may all affect immune reconstitution. According to report, 10–40% of HIV-1-infected patients fail to restore the normalization of CD4+ T cell count and function. They are referred to as immunological non-responders (INRs) who fail to achieve complete immune reconstitution and have a higher mortality rate and higher risk of developing other non-AIDS diseases compared with those who achieve complete immune reconstitution. Heretofore, the mechanisms underlying incomplete immune reconstitution in HIV remain elusive, and INRs are not effectively treated or mitigated. This review discusses the recent progress of mechanisms and factors responsible for incomplete immune reconstitution in AIDS and summarizes the corresponding therapeutic strategies according to different mechanisms to improve the individual therapy.